Identification of a New Target slr0946 of the Response Regulator Sll0649 Involving Cadmium Tolerance in Synechocystis sp. PCC 6803 - Sun, Tao; Xu, Le; Wu, Lina; Song, Zhongdi; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2017)
Survival of photosynthetic cyanobacteria is challenged by environmental contaminations like heavy metals. Among them, deciphering the regulatory mechanisms for cadmium (Cd) in cyanobacteria would facilitate the construction of Cd-resistant strains. In this study, the DNA-Affinity-Purified-chromatin immunoprecipitation assay was employed to identify the direct targets of Sll0649, which was a Cd2+-related response regulator identified in our previous work in model cyanobacteria Synechocystis sp. PCC 6803. As a result, the promoter region of slr0946 encoding the arsenate reductase was enriched 4-folds by quantative real time PCR analysis. Further, deletion of slr0946 led to a sensitive phenotype to Cd2+ stress compared with the wild type (WT) and the sensitive phenotype of Δslr0946 could be rescued by complementation assay via introducing slr0946 back into Δslr0946. Finally, individually overexpression of slr0946 as well as two Cd2+-related genes identified priviously (i.e., sll1598 and slr0798) in WT could significantly improve the tolerance of Synechocystis sp. PCC 6803 to Cd2+. This study provided a better understanding of the tolerance mechanism to Cd2+ in cyanobacteria and also feasible strategies for tolerance modifications to heavy metals in the future.